Cleaning frequency of the solar PV power plant for maximum energy harvesting and financial profit - Mohamed R. Said; Adel A. El-Samahy; Helmy M. El Zoghby (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
Cleaning frequency of the solar PV power system plays a major role in energy harvesting. This paper proposed an optimized cleaning frequency for the PV power plants. The objective is to maximize energy harvesting and increase financial profit. The proposed technique is tested in roof top grid connected 20 kW PV power plant in Cairo, Egypt. Experimental results are collected for one year throw the period from January 2021 to December 2021 based on real time monitoring under the regular cleaning of the PV plant every fifteen days. The collected data and results are used for deriving a formula to find the optimal frequency for cleaning the PV cells. This formula can be used for any PV power plant under different operating conditions. Therefore, the formula can detect the financial losses due to the dust accumulated on the surfaces of PV panels. The model proposed in this research is verified by the comparison between the generated power from the photovoltaic power plant and the cost of cleaning (water and cleaning workers) in case of manual cleaning, taking into consideration the various operating conditions though whole the period of the study.